Utilization of Molasses Waste as Activated Carbon for Adsorption of Rhodamine B from Synthetic Waste - Ali Nur Muhammad Zaidin Balatif; Muhammad Muhammad; Rizka Mulyawan (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
The utilization of molasses waste as Rhodamine B adsorbent has been investigated by studying adsorption isotherm and adsorption kinetics. The sample used is a variation of the concentration of Rhodamine B 10, 25, and 50 mg/L for kinetics adsorption and 50 mg/L, 100 mg/L, 150 mg/L, 200 mg/L, and 250 mg/L for isotherm adsorption. Kinetic analysis adsorption being tested by pseudo-first-order and pseudo-second-order rate equation, as for the equilibrium equation being tested by Langmuir and Freundlich adsorption isotherms. Study shows that Langmuir equation model and pseudo-second-order are the most suitable to be applied. The adsorption constant is obtained of 1.1664 L/g and qmax of 221.8279 mg/g in Langmuir Equation. Whereas for pseudo second order equations obtained values of qe, exp and qe, cal which are slightly different. The qe, cal values obtained were 8.142 mg/g, 23.141 mg/g, and 53.895 mg/g for various concentrations.  K value is obtained with a range of 0.001754-0.000294 and a value of R2 with a range of 0.8249-0.995 for various concentration. Intraparticle diffusion in this study is not the only rate control measure due to the plot linear at each concentration does not cross the origin.